(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2025)
This study examines the transformation of the traditional leadership system of the Murut community in North Borneo (now Sabah) during British administration, focusing on changes in the structure, function and roles of traditional leaders, as well as the emergence of modern leaders. Although there are studies on the Murut community, understanding of how their leadership system adapted to colonial influence remains limited. This study addresses the question of how British modern administration influenced the traditional leadership system of the Murut. The findings of the study show that Murut’s traditional leadership institutions centred on the tribal system have undergone significant changes through the implementation of government policies such as the Village Administration Proclamation 1891, the Native Chief Classification Scheme 1912 and the Indigenous Administration Ordinance 1937. Traditional leaders including Orang Tua and tribal chiefs were either replaced or incorporated into modern administrative roles such as Village Headmen and Native Chiefs. These positions were assigned new responsibilities, which included the management of Native Courts. This study employs a historiographical approach with qualitative and descriptive methods, analysing primary documents such as The British North Borneo Herald, North Borneo Secretariat Files, and Colonial Office records, as well as secondary sources. This study makes an important contribution to understanding the transformation and modernisation of Murut leadership under British influence and its implications for the socioeconomic aspects of the Murut community. Further research is needed to explore the role of modern Murut leaders in the post-independence era. Kajian ini meneliti transformasi sistem kepimpinan tradisional masyarakat Murut di Borneo Utara (kini Sabah) semasa pentadbiran British dengan fokus terhadap perubahan struktur, fungsi dan peranan pemimpin tradisional serta kemunculan golongan pemimpin moden. Walaupun terdapat kajian mengenai masyarakat Murut, pemahaman tentang adaptasi sistem kepimpinan mereka terhadap pengaruh kolonial masih terhad. Kajian ini menjawab persoalan bagaimana pentadbiran moden British mempengaruhi sistem kepimpinan tradisional Murut. Dapatan kajian menunjukkan bahawa institusi kepimpinan tradisional Murut yang berpusat pada sistem suku mengalami perubahan signifikan melalui pelaksanaan dasar kerajaan antaranya seperti Proklamasi Pentadbiran Kampung 1891, Skim Klasifikasi Ketua Anak Negeri 1912 dan Ordinan Pentadbiran Peribumi 1937. Pemimpin tradisional iaitu Orang Tua dan ketua suku digantikan atau disepadukan dalam jawatan pentadbiran moden yang dikenali sebagai Ketua Kampung dan Ketua Anak Negeri dengan tanggungjawab baharu seperti pengendalian Mahkamah Anak Negeri. Kajian ini menggunakan pendekatan historiografi dengan kaedah kualitatif dan deskriptif serta menganalisis dokumen primer seperti The British North Borneo Herald, North Borneo Secretariat File dan rekod Colonial Office serta sumber sekunder. Kajian ini memberikan sumbangan penting dalam memahami transformasi dan modenisasi kepimpinan Murut di bawah pengaruh British dan implikasinya terhadap sosioekonomi masyarakat Murut. Kajian lanjut diperlukan untuk meneliti peranan pemimpin moden Murut dalam era pasca-kemerdekaan.